Pregnancy test and measurements related to miscarriages among experienced pregnant women in Indonesia - Supriatin, Supriatin; Wahyuni, Nuniek Tri; Herawati, Cucu; Indragiri, Suzana; Amaliah, Lili (Science Midwifery, 2024)
Miscarriage is one of the major reproductive health problems that contribute to maternal morbidity and mortality in Indonesia. This study aims to explore the relationship between prenatal check-ups, medical measurements, and the risk of miscarriage in women who have experienced pregnancy. Using data from the Indonesian Family Life Survey (IFLS) 2014-2015, this study involved 14,952 female respondents. Multivariate analysis showed that age, hemoglobin test, fetal height measurement, blood pressure measurement, tetanus toxoid (TT) injection, and iron supplementation significantly affected the risk of miscarriage (p < 0.05). The main findings of this study were the age, Hb test, fetal height examination, pelvic examination, weighing, height measurement, blood pressure measurement, administration of TT injections, and administration of iron pills associated with miscarriages among experienced pregnant women. However, limited access to health services and low levels of education about the importance of early pregnancy check-ups remain significant challenges, especially in rural areas. This study recommends increasing public awareness, education, and access to reproductive health services as an effort to reduce miscarriage rates in Indonesia.